Arsenic-induced neurotoxicity: A mechanistic appraisal - Garza-Lombó, Carla (J Biol Inorg Chem, 2019)
Arsenic is a metalloid found in groundwater as a byproduct of soil/rock erosion and industrial and agricultural processes. This xenobiotic elicits its toxicity through different mechanisms, it has been identified as a toxicant that affects virtually every organ or tissue in the organism. In the central nervous system exposure to arsenic can induce cognitive dysfunction, it has been linked to several neurological disorders, including neurodevelopmental alterations, and is considered a risk factor for neurodegenerative disorders. However, the exact mechanisms involved are still unclear. In this review, we aim to appraise the neurotoxic effects of arsenic and the molecular mechanisms involved. First, we discuss the epidemiological studies reporting on the effects of arsenic in intellectual and cognitive function during development as well as studies showing the correlation between arsenic exposure and altered cognition and mental health in adults. The neurotoxic effects of arsenic and the potential mechanisms associated with neurodegeneration are also reviewed including data from experimental models supporting epidemiological evidence of arsenic as a neurotoxicant. Next, we focused on recent literature regarding arsenic metabolism and the molecular mechanisms that begin to explain how arsenic damages the central nervous system; including, oxidative stress, energy failure and mitochondrial dysfunction, epigenetics, alterations in neurotransmitter homeostasis and synaptic transmission, cell death pathways and inflammation. Outlining the specific mechanisms by which arsenic alters the cell function is key to understand the neurotoxic effects that convey cognitive dysfunction, neurodevelopmental alterations and neurodegenerative disorders.